2012
DOI: 10.4028/www.scientific.net/amm.229-231.78
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Effect of Ethanol on Diesel HCCI Combustion Using Multi-Zone Model

Abstract: This study investigates the potential of controlling diesel homogenous charge compression ignition (HCCI) combustion by blending ethanol, which inhibits low temperature oxidation offering the possibility to control ignition in HCCI combustion. The simulation results from a multi-zone model show that the ethanol reduces the key active intermediate radicals OH, CH2O, H2O2, delays the low temperature oxidation reaction (LTR), reduces the heat released during LTR stage. As a result, it retards the main combustion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Several engine combustion studies [48,51,52] have shown that ethanol suppresses LTHR, but this was rationalized as a thermodynamic, or charge cooling affect; the underlying chemistry of ethanol as a radical scavenger is often overlooked. Here, the attempt was to provide a more fundamental explanation of the chemical kinetics of PRF mixtures with ethanol.…”
Section: Resultsmentioning
confidence: 99%
“…Several engine combustion studies [48,51,52] have shown that ethanol suppresses LTHR, but this was rationalized as a thermodynamic, or charge cooling affect; the underlying chemistry of ethanol as a radical scavenger is often overlooked. Here, the attempt was to provide a more fundamental explanation of the chemical kinetics of PRF mixtures with ethanol.…”
Section: Resultsmentioning
confidence: 99%